Sex trafficking and sex-for-food/money: terrorism and conflict-related sexual violence against men in the Lake Chad region. Issue 1 (2nd January 2022) - Njoku, Emeka Thaddues; Akintayo, Joshua; Mohammed, Idris
ABSTRACT: In understanding conflict-related sexual violence (CRSV), the notion of how sexuality and sex are naturally linked to power is gaining traction in IR discourses. There is, however, little contextual or empirical evidence that accounts for the various forms of CRSV against men, or how offenders exploit power dynamics in conflict and post-conflict settings to achieve their sexual desires. As a result, we rely on ethnographic accounts from survivors/victims, NGO workers, and security personnel on the front lines of the counter-terrorism campaign in the Lake Chad basin, particularly in North-eastern Nigeria. Long-term terrorist violence, we argue, creates material imbalances in men and boys and increases their vulnerabilities, providing platforms for individual perpetrators to exploit their vulnerable status or engage in sex-trafficking rings to satisfy their sexual urges. Therefore, this article adds conceptually and empirically to the nature and motivations of wartime sexual violence, as well as the gendered dynamics of armed conflict. It challenges the popular masculinist notion that men are immune to sex trafficking and sexual violence. The study emphasises the importance of effective IDP camp management and prosecution in preventing would-be offenders.